Implementasi Sistem Informasi Pengarsipan Dokumen Berbasis Web Pada Sub Dinas Dukungan Operasi Dan Latihan (Subdisdukopslat) - Christoper Dendra; Alcianno G. Gani; Muryan Awaludin (Jurnal Mahasiswa Informatika dan Desain, 2025)
The Indonesian Air Force is supported in its operations and training by Sub Dinas Dukungan Operasi Dan Latihan (Subdisdukopslat). Archives are significant records that are kept so they will be simple to locate in the future. Subdisdukopslat places a great deal of importance on archives, hence a smooth, quick, and efficient archive administration procedure is expected. Inadequate management of the archives might affect the ease of finding information, which can hinder subsequent stages of the project. As a result, an effective and proper management system must be used to handle archives and official documents. The analysis and creation of a web-based document filing information system that meets Subdisdukopslat's needs is covered in this study. This information system's design is derived from a system design that has been assembled, which includes activity, sequence, and use case diagrams. All documents up to letters are logged in books and stored in a dedicated cabinet as part of Subdisdukopslat's manual official document filing system. It is therefore believed that this technology will assist Subdisdukopslat in handling official document archives.